Optimation of Adsorpsi and Desorpsi of Mn2+ Ions on Gel-GPTMS Silica (Glycidoxypropyltrimethoxysilane) Modified with Sulfonates - Azizah, Ayu; Oktavia, Budhi; Dewata, Indang; Away, Romy Dwipa Yamesa (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Silica gel is an adsorbent often used in chromatography columns as a resin or stationary phase. Silica gel has active groups on its surface in the form of silanol (-SiOH) and siloxane (-Si-O-Si-). The effectiveness of silica gel in absorbing heavy metal ions is very low, so modification is needed to increase the absorption capacity of silica gel to metal ions. The addition of sulfonate with the GPTMS linkage compound dose modification. Adsorption and desorption are two methods that can be used to separate manganese metal. This research aims to obtain the optimum desorption agent (NaCl and CaCl2) and the concentration of the AAS-characterised desorption agent. This study used the column method for the adsorption and desorption process. This study used the column method for the adsorption and desorption process. The column method is a technique used to separate certain substances from a mixture by utilizing the interaction between adsorbent and adsorbate. The results obtained optimum desorption agent CaCl2 where the weight desorbed 0.1168002 mg with a percent desorption of 92.3%, the optimum concentration of CaCl2 0.05 M where the weight desorbed 0.132264 mg with a percent desorption of 95% Adsorbent characterization was conducted with FTIR and XRF.